An overview of Teletandem mediation courses for teacher education - Souza, Micheli Gomes De; Zakir, Maisa De Alcântara [UNESP]; Garcia, Daniela Nogueira De Moraes [UNESP] (Pontifícia Universidade Católica de São Paulo - PUC-SP, 2021)
This paper aims to investigate practices in teacher education in the context of the Teletandem Brasil Project (Vassallo & Telles, 2006). Through web conferencing tools, the project pairs up Brazilian university students learning foreign languages with foreign university students learning Portuguese. The partnerships are supported by mediation sessions conducted by professors and researchers of the Teletandem Project. In this paper, we present some theoretical concepts related to telecollaboration (Belz, 2003; O’Dowd, 2007; 2018), besides providing a detailed description and comparison of four editions of preparatory courses for teletandem mediators, organized by researchers of the project. The results of the analysis may provide alternatives for teacher education in a context of growing transcultural connections.

Este artigo busca investigar práticas de formação de professores no contexto do projeto Teletandem Brasil (Vassallo & Telles, 2006). Por meio de ferramentas de webconferência, o projeto emparelha estudantes universitários brasileiros que aprendem uma língua estrangeira com estudantes universitários estrangeiros que aprendem português. As parcerias são apoiadas por sessões de mediação conduzidas por professores e pesquisadores do projeto Teletandem. Neste artigo, apresentamos alguns conceitos teóricos relacionados à telecolaboração (Belz, 2003; O’Dowd, 2007; 2018), além de fazer uma descrição e comparação detalhadas de quatro edições de cursos para mediadores de teletandem, organizadas por pesquisadores do projeto. Os resultados da análise podem fornecer alternativas para a formação de professores em um contexto de crescentes conexões transculturais.
Um panorama de cursos de mediação em Teletandem para a formação de professores
Keywords: Teletandem; Mediation; Teacher education; Course design; Teletandem; Mediação; Formação de professores; Elaboração de cursos